Interpretation of L.Shestov works as philosophical and religious problem - Конотоп, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to the important problem, the problem of philosophical and theological interpretation. The selected works of the famous philosopher – L. Shestov are chosen as a main object of this interpretation. It is his philosophy, which he described as "a journey through the human souls", draws attention until now.